2007
DOI: 10.1021/bi700233k
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of an Amyloid-Forming Protein During Photoinitiated Hexamer−Dodecamer Transitions Revealed through Small-Angle Neutron Scattering

Abstract: Shape-reconstruction analysis applied to small angle neutron scattering (SANS) data is used to determine the in vitro conformations of alpha-chymotrypsin oligomers that form as a result of partial unfolding with a photoresponsive surfactant. In the presence of the photoactive surfactant under visible light, the native oligomers (dimers or compact hexamers) rearrange into expanded corkscrew-like hexamers. Converting the surfactant to the photopassive form with UV light illumination causes the hexamers to latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…For example, polyvalent trehalose with a short alkyl chain (2) showed a strong inhibitory effect, but polyvalent trehalose with a longer alkyl chain (3) induced amyloid formation. It has been reported that amyloid formation is induced by surfactants of amphiphilic molecules [25][26][27]. Not only the saccharide structure of the polymer but also amphiphilicity plays important roles in the amyloid formation and inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polyvalent trehalose with a short alkyl chain (2) showed a strong inhibitory effect, but polyvalent trehalose with a longer alkyl chain (3) induced amyloid formation. It has been reported that amyloid formation is induced by surfactants of amphiphilic molecules [25][26][27]. Not only the saccharide structure of the polymer but also amphiphilicity plays important roles in the amyloid formation and inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary studies with trans -azoTAB have also provided evidence that trans -azoTAB can bind more strongly than cis -azoTAB to hydrophobic domains of some proteins, and lead to light-induced changes in the secondary, 46 tertiary, 5, 90 and quaternary structure 91 (i.e., degree of unfolding of proteins). For bovine serum albumin, a series of structural transitions was indentified, and addition of trans -azoTAB led to transitions between the structural states denoted as N, N d , F and E. The concentrations required for trans -azoTAB to cause the N to N d , N d to F, and F to E were 0.55mM, 0.8mM and 2.83mM, respectively.…”
Section: Light-sensitive Surfactantsmentioning
confidence: 99%
“…This proposition has led to a series of recent investigations in which the interactions of azobenzene-based surfactants with DNA 32, 88, 89 or proteins 5, 46, 47, 90, 91 have been reported.…”
Section: Light-sensitive Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under visible light, ~75% of azoTAB adopts the relatively hydrophobic trans conformation, while under UV light ~90% of the surfactant exists as the relatively hydrophilic cis isomer. This provides a means to photoreversibly control protein‐surfactant interactions, as demonstrated by our previous studies . In the case of carbonic anhydrase, for example, the protein was found to dramatically unfold and, thus, inactivate in the presence of the trans surfactant, while the unfolding was reversed to a native‐like enzyme conformation and activity upon UV illumination, resulting in enzyme reactivation .…”
Section: Introductionmentioning
confidence: 65%